De novo Drug Delivery Modalities for Treating Damaged Hearts: Current Challenges and Emerging Solutions - Alvi, Syed Baseeruddin; Ahmed, Salmman; Sridharan, Divya; Naseer, Zahra; Pracha, Nooruddin; Wang, Henry; Boudoulas, Konstantinos Dean; Zhu, Wuqiang; Sayed, Nazish; Khan, Mahmood (Frontiers in Cardiovascular Medicine, 2021)
Cardiovascular disease (CVD) is the leading cause of mortality, resulting in approximately one-third of deaths worldwide. Among CVD, acute myocardial infarctions (MI) is the leading cause of death. Current treatment modalities for treating CVD have improved over the years, but the demand for new and innovative therapies has been on the rise. The field of nanomedicine and nanotechnology has opened a new paradigm for treating damaged hearts by providing improved drug delivery methods, specifically targeting injured areas of the myocardium. With the advent of innovative biomaterials, newer therapeutics such as growth factors, stem cells, and exosomes have been successfully delivered to the injured myocardial tissue, promoting improvement in cardiac function. This review focuses on three major drug delivery modalities: nanoparticles, microspheres, and hydrogels, and their potential for treating damaged hearts following an MI.